2012
DOI: 10.1140/epjb/e2011-20538-6
|View full text |Cite
|
Sign up to set email alerts
|

Defects in hexagonal-AlN sheets by first-principles calculations

Abstract: Abstract. Theoretical calculations focused on the stability of an infinite hexagonal AlN (h-AlN) sheet and its structural and electronic properties were carried out within the framework of DFT at the GGA-PBE level of theory. For the simulations, an h-AlN sheet model system consisting in 96 atoms per super-cell has been adopted. For h-AlN, we predict a lattice parameter of 1.82 Å and an indirect gap of 2.81 eV as well as a cohesive energy which is by 6% lower than that of the bulk (wurtzite) AlN which can be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 28 publications
10
64
1
Order By: Relevance
“…1d). The good agreement of the properties of single-layer h-AlN obtained here with previous studies dedicated to this system [9,10], emphasizes the appropriateness of the level of theory chosen in this work for modeling stacks of h-AlN with graphene. Two-layer h-AlN can adopt five different stacking configurations following commonly introduced stacking configurations and notations [9]: two stacking configurations result as the hexagons of one layer reside on the hexagons of the other layer, e.g., Al over Al and N over N (AA), and Al over N and N over Al (AA'); other three stacking configurations result as the hexagons of one layer are translated with respect to the hexagons of the other layer, e.g., AB, AB', and A'B, Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…1d). The good agreement of the properties of single-layer h-AlN obtained here with previous studies dedicated to this system [9,10], emphasizes the appropriateness of the level of theory chosen in this work for modeling stacks of h-AlN with graphene. Two-layer h-AlN can adopt five different stacking configurations following commonly introduced stacking configurations and notations [9]: two stacking configurations result as the hexagons of one layer reside on the hexagons of the other layer, e.g., Al over Al and N over N (AA), and Al over N and N over Al (AA'); other three stacking configurations result as the hexagons of one layer are translated with respect to the hexagons of the other layer, e.g., AB, AB', and A'B, Fig.…”
Section: Resultssupporting
confidence: 80%
“…Our theoretical study on the structural and electronic properties of single layers of h-AlN further involved the incorporation of selected point defects (e.g., vacancies, as well as substitutional atoms of silicon and carbon) providing the prospect for deliberate tailoring of its electronic properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…2. The average (Al-N) bond length is 1.811 Å parallel with the tube axis, and another is 1.818 Å diagonal to the tube axis which is in agreement with other researches [27,[32][33][34][35]. With doping of B atom, the bond lengths (Al-N) decrease significantly to 1.48 Å and with doping of As the bond lengths increase significantly to 2.369 Å .…”
Section: Structural Parameterssupporting
confidence: 90%
“…Almeida et al 30 investigated properties of defects, such as vacancies, antisites, and impurities, in h-AlN. It was reported that N vacancies and Si impurities lead to the breaking of the planar symmetry and cause significant changes in the electronic properties.…”
Section: -29mentioning
confidence: 99%